Temperature increase and its effects on fish stress physiology in the context of global warming. Issue 6 (13th November 2020) - Alfonso, Sébastien; Gesto, Manuel; Sadoul, Bastien
Abstract: The capacity of fishes to cope with environmental variation is considered to be a main determinant of their fitness and is partly determined by their stress physiology. By 2100, global ocean temperature is expected to rise by 1–4°C, with potential consequences for stress physiology. Global warming is affecting animal populations worldwide through chronic temperature increases and an increase in the frequency of extreme heatwave events. As ectotherms, fishes are expected to be particularly vulnerable to global warming. Although little information is available about the effects of global warming on stress physiology in nature, multiple studies describe the consequences of temperature increases on stress physiology in controlled laboratory conditions, providing insight into what can be expected in the wild. Chronic temperature increase constitutes a physiological load that can alter the ability of fishes to cope with additional stressors, which might compromise their fitness. In addition, rapid temperature increases are known to induce acute stress responses in fishes and might be of ecological relevance in particular situations. This review summarizes knowledge about effects of temperature increases on the stress physiology of fishes and discusses these in the context of global warming.